Asset management insights : phases, practices, and values - Azevedo, Celso de (Industrial Press, Inc., 2019)
Uniquely organised, Asset Management Insights follows the life cycle of industrial assets and infrastructures. The book reviews the thematic components of asset management both from a conceptual point of view and from the point of view of its practical application.